2015
DOI: 10.5114/wo.2014.47131
|View full text |Cite
|
Sign up to set email alerts
|

Review Selenium as a marker of cancer risk and of selection for control examinations in surveillance

Abstract: Publication is summarization of existing data being results of literature review and our experience on usefulness of selenium as a diagnostic marker selection for control examinations in surveillance and as a marker of patients with high risk of cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Geographical differences can cause discrepancies. The average Se level in North America is 122.4–151.8 μg/L, while the level in the serum / plasma of Poles is about 70 μg/L; in some regions, it is even 50–55 μg/L [2,32,33,34]. In our control (normotensive group), the mean Se level in the serum in the 10–14th pregnancy week was 62.89 μg/L (range 41.14–125.54 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Geographical differences can cause discrepancies. The average Se level in North America is 122.4–151.8 μg/L, while the level in the serum / plasma of Poles is about 70 μg/L; in some regions, it is even 50–55 μg/L [2,32,33,34]. In our control (normotensive group), the mean Se level in the serum in the 10–14th pregnancy week was 62.89 μg/L (range 41.14–125.54 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…In many research papers devoted to the study of the mechanisms of endogenous neuroprotection under conditions of ischemia, the resumption of the work of the glutathione unit of the thiol-disulfide system (TDS) during an increase in the level of HSP70 is noted, and the administration of exogenous HSP70 leads to an increase in the functional activity of the glutathione system in ischemic neurons of experimental animals ( Hacke et al, 2008 ). Thus, under conditions of ischemia, HSP70 proteins mobilize antioxidant resources in neurons by increasing the level of both the cytosolic and mitochondrial pool of reduced glutathione ( Lener et al, 2015 ). Recently, data have appeared on the role of HSP in the stabilization of HIF-1a, which, under conditions of ischemia, is responsible for ensuring the processes of proliferation, apoptosis, angiogenesis, and stabilization of protein molecules under conditions of oxidative stress.…”
Section: The Role Of Hsp70 Proteins In the Mechanisms Of Endogenous N...mentioning
confidence: 99%
“…A number of research papers determine the effectiveness of sodium selenite in myocardial infarction. Selenium compounds have an immunomodulating, radioprotective effect due to the function of glutathione peroxidase, which provides the recovery of hydroperoxides and other products of free radical reactions and regulates the release of lipoxygenase and cyclooxygenase metabolites of arachidonic acid ( Koszta et al, 2012 ; Costa et al, 2014 ; Lener et al, 2015 ; Okuyama et al, 2015 ).…”
Section: Possible Pathways For Activation Of Hsp70-dependent Mechanis...mentioning
confidence: 99%
“…Concentrations above 90 μg/L were associated with a higher risk of cancer, but the changes were not statistically significant [ 5 ]. However, Lenar et al indicated that the risk of developing lung cancer increases with decreasing serum selenium concentrations, taking a concentration of 70 μg/L as the cutoff value [ 6 ]. The authors also pointed out that determining the optimal serum selenium concentration is geographically and populationally variable [ 6 ].…”
Section: Introductionmentioning
confidence: 99%